Increasing Student Learning Motivation through of the Dick and Carey Model in Islamic Religious Education - Nugraha, Mulyawan Safwandy; Purnasari, Martina; Dedih, Ujang (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2023)
This research focuses on addressing the persistent challenge of motivating students in their engagement with Islamic Religious Education (PAI) materials. Despite the overarching goal of instilling virtue, there remains a recurring issue of insufficient motivation among students when it comes to PAI content. In response, this study investigates the potential effectiveness of applying the Dick and Carey instructional model within the context of GIS Prima Insani Elementary School. Employing a qualitative case study methodology, the research highlights the Dick and Carey model's systematic and organized approach. This instructional model emphasizes transparent steps that contribute to the clarity of learning outcomes, encouraging students to apply acquired knowledge in their daily lives—aligned with the broader objective of Islamic religious education. The findings suggest that the Dick and Carey model is well-suited for educational settings, offering a clear direction for both educators and students and fostering a sense of recognition and support. The structured nature of the model contributes to heightened commitment among students, ultimately enhancing motivation and facilitating optimal learning outcomes. In conclusion, the study underscores the significance of implementing effective instructional models, particularly the Dick and Carey approach, in Islamic religious education. By nurturing motivation and aligning with established standards, this model emerges as a valuable tool for educators, contributing to an overall enhanced educational experience. The findings emphasize the importance of adopting innovative approaches to address challenges in Islamic religious education, paving the way for future research and improvements in pedagogical practices